2017
DOI: 10.1001/jamafacial.2016.2120
|View full text |Cite
|
Sign up to set email alerts
|

Association of Upper Eyelid Ptosis Repair and Blepharoplasty With Headache-Related Quality of Life

Abstract: be a functional indication for ptosis repair and blepharoplasty. OBJECTIVE To evaluate the changes in headache-related quality of life in patients who underwent upper eyelid ptosis repair or blepharoplasty. DESIGN, SETTING, AND PARTICIPANTS A prospective cohort study was conducted among 108 patients who underwent standard upper eyelid blepharoplasty and 44 patients who underwent ptosis repair (levator resection, Müller muscle resection, or frontalis suspension) for obscuration of the superior visual field at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Twenty-seven patients were needed per treatment group to detect a difference of 8.3 in the HIT-6 score between groups A and B at 6 and 12 months, with a two-sided 5% significance level and a power of 85%, allowing for a 15% attrition rate and 10% for possible non-parametric testing (G* Power version 3.1.9.6, University of Kiel, Germany). The mean HIT-6 score is based on pre-and postoperative differences between two groups, i.e., the blepharoplasty and ptosis surgery groups [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-seven patients were needed per treatment group to detect a difference of 8.3 in the HIT-6 score between groups A and B at 6 and 12 months, with a two-sided 5% significance level and a power of 85%, allowing for a 15% attrition rate and 10% for possible non-parametric testing (G* Power version 3.1.9.6, University of Kiel, Germany). The mean HIT-6 score is based on pre-and postoperative differences between two groups, i.e., the blepharoplasty and ptosis surgery groups [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“… 1 2 3 4 5 Majority of Japanese plastic surgeons that use it tend to be most interested in eyelid fold contour, pretarsal show, and eyebrow height. IB treatment therefore tends to be categorized as “cosmetic” rather than “functional.” 6 7 …”
Section: Introductionmentioning
confidence: 99%
“…As a result of tonic reflexive contraction of the occipitofrontalis muscle, ptosis patients may also experience tension-related headaches [7][8][9]. Similarly, Simsek reported that surgery for ptosis and blepharoptosis provided significant relief from tension-related headaches, and resulted in an improved quality of life [10].…”
Section: Introductionmentioning
confidence: 99%